2020
DOI: 10.1177/0034644620933803
|View full text |Cite
|
Sign up to set email alerts
|

Energy Consumption, Carbon Emission, and Well-Being in Africa

Abstract: The link among energy use, human welfare, and carbon emission has been a topical issue in the literature. In Africa, energy consumption has been on the increase owing to the production and consumption of sophisticated consumer goods and home appliances. Increased energy use triggers carbon emission that is detrimental to human welfare. This study investigates this puzzle in emerging African countries by utilizing panel vector autoregressive and system generalized method of moments (SYS-GMM) in the context of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…According to the findings, economic expansion, increased reliance on information and communications technology, and increased energy consumption are all factors that are driving up carbon emissions, whereas international trade and the utilization of renewable energy sources are driving down carbon emissions. In a similar vein, several models show that foreign direct investment can either have a positive or negative impact on the amount of carbon dioxide emissions [ 33 ] used systematic generalized method of moments models and vector autoregressive models for his research on energy consumption and carbon emissions in Africa. The findings indicated that there was a one-way causative association between coal and mortality, as well as a one-way causal relationship between coal and per capita income and fuel consumption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to the findings, economic expansion, increased reliance on information and communications technology, and increased energy consumption are all factors that are driving up carbon emissions, whereas international trade and the utilization of renewable energy sources are driving down carbon emissions. In a similar vein, several models show that foreign direct investment can either have a positive or negative impact on the amount of carbon dioxide emissions [ 33 ] used systematic generalized method of moments models and vector autoregressive models for his research on energy consumption and carbon emissions in Africa. The findings indicated that there was a one-way causative association between coal and mortality, as well as a one-way causal relationship between coal and per capita income and fuel consumption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wang et al [21] used the PSR approach and factor weight ranking method to assess ecologically responsible development. Olubiyi [22] uses the Generalized System Torque (SYS-GMM) approach to analyze the link between energy consumption, carbon dioxide emissions, and welfare. e findings reveal a one-way causal relationship between coal use and per capita revenue.…”
Section: Literature Reviewmentioning
confidence: 99%